Point-of-Care Ultrasound-Guided Aspiration of the Hip Joint by an Emergency Medicine Physician: A Pediatric Retrospective Case Series. Issue 3 (March 2022) - Berant, Ron; Bder, Moad; Kaufman-Shriqui, Vered; Shahar-Nissan, Keren
Abstract : Objectives: Early administration of antibiotics is crucial to treating septic hip. This study aimed to describe the clinical course and outcomes of children with septic hip diagnosed using point-of-care ultrasound (POCUS)–guided hip aspirations performed by an emergency medicine physician. Methods: A retrospective case series analysis. Results: Between January 1, 2014, and December 31, 2019, 10 children with septic hip were diagnosed by emergency physicians using POCUS-guided hip aspirations. Six of them were female; the mean age was 4.2 ± 4.5 years, and the mean time from onset of symptoms to diagnosis was 2.9 ± 1.7 days. Seven patients (70%) had a history of fever. All the patients had elevated inflammatory blood markers (white blood cell count >12 K/μL, erythrocyte sedimentation rate >40 mm/h, or a C-reactive protein >2 mg/dL). The mean time from hospital arrival to the first antibiotic dose was 5.2 + 4.0 hours. All the children were discharged fully ambulatory and did not require rehospitalization or repeat aspiration after discharge. Conclusions: This case series shows that POCUS-guided hip aspiration is both safe and feasible in diagnosing septic hip in the pediatric emergency department. The procedure enables rapid diagnosis and early initiation of antibiotic treatment, thus reducing the risk for complications related to delayed initiation of therapy.